(untitled) - Huỳnh, Đặng Bảo Trinh (Cần Thơ, 2010)
The study aims at testing the effects of the implementation of the video clips and images to teaching and learning reading on learners' quality of EFL reading and investigating learners' attitudes towards the use of the video clips images in their reading class.
Keywords: Reading comprehension,Tiếng Anh,Đọc hiểu,English language; Dạy và học,Người học ngoại ngữ,Study and teaching,Foreign speakers